"Es muß besser werden!". Aby und Max Warburg im Dialog über Hamburgs geistige Zahlungsfähigkeit - Michels, Karen (Mäzene für Wissenschaft, 2015)
The story of how Max Warburg became head of the family-owned bankhouse, although his brother was supposed to take over the business, was often told: When he was 12 years old, the one year older Aby offered Max his birthright for the promise to buy all the books Aby would ever need. Max accepted,and - as he later said - issued "the biggest blank cheque in my life". The paths of life of the two brothers spilt into different directions. Aby built his library into a research institute. Max developed M. M. Warburg & Co., thus the bankhouse becoming one of the most important private banks in Germany. At Simultaneously, they both pursued another goal: the foundation of the university. The brothers were among the early donors of the Hamburg Scientific Foundation (Hamburgische Wissenschaftliche Stiftung). It was all about "Hamburg's mental capacity" ("Hamburgs geistige Zahlungsfähigkeit").